Synthesis of new bis[1-(thiophenyl)propynones] as potential organic dyes for colorless luminescent solar concentrators (LSCs). (March 2020) - Albano, Gianluigi; Colli, Tony; Nucci, Luigi; Charaf, Rima; Biver, Tarita; Pucci, Andrea; Aronica, Laura Antonella
Abstract: New luminophores having different aryl nuclei and propynones moieties have been obtained via Sonogashira reactions. Their optical properties were evaluated and indicated that carbonyl groups are responsible for significant bathochromic effects and high Stokes shifts. The insertion of -OMe groups on the central benzene unit gives to the fluorophore high optical efficiency (7.7%) when homogeneously dispersed in a poly(cyclohexyl methacrylate) (PCMA) film and connected to a PV cell. Graphical abstract: Image 1 Highlights: New bis[1-(thiophenyl)propynones were easily obtained via Sonogashira reactions. Photophysical properties of all fluorophores were investigated. Carbonyl groups seemed to be responsible for significant bathochromic effects and high Stokes shifts . Important solvatochromism was observed when dimethoxy functional groups were linked to the central benzene ring. A PCMA film of 3, 3'-(2, 5-dimethoxy-1, 4-phenylene)bis(1-(thiophen-2-yl)prop-2-yn-1-one) showed promising optical efficiencies.